Perfluoroinated Ionomer as an Artificial SEI for Silicon Nano-Flake Anode in LiTFSI/Tetraglyme Solvate Ionic Liquid. Issue 2 (4th February 2022) - Haruta, Masakazu; Konaga, Hiroto; Doi, Takayuki; Inaba, Minoru
Abstract : Cycle performance of silicon nano-flake powder (LeafPower ® Si) anodes was improved by coating of perfluorosulfonic acid (PFSA) polymers (Nafion ® and Aquivion ® ) as an artificial solid electrolyte interphase (SEI). The Si electrodes were coated with PFSA ionomer by addition of PFSA ionomer solution to aqueous slurry of the Si composite electrode. H + -type Nafion ® -coated Si electrodes demonstrated improved capacity retentions and Coulombic efficiencies owing to the formation of a LiF-rich SEI composed of reductive decomposition products of Nafion ® . The Nafion ® coating suppressed the increase in polarization and the electrode swelling upon cycling because the LiF-rich SEI effectively suppressed electrolyte decomposition. Li + and Cs + -type Nafion ® and H + -type Aquivion ®, which has a shorter side chain than Nafion ®, provided similar positive effects on cycle performance of the Si electrodes. Furthermore, the Si electrodes achieved good cycleability up to 500 cycles owing to synergy effects of the Nafion ® coating and an SEI-forming additive of fluoroethylene carbonate (FEC).